Sistem Aplikasi Pemesanan Motor Berbasis Android pada Wahana Ritel Honda Ciracas - Wike Rahayu; Niki Ratama (Journal of Research and Publication Innovation, 2024)
This research aims to design and implement an Android-based motorbike ordering and sales application system at Wahana Ritel Honda Ciracas. The identified problems revolve around the unorganized data of motorbike orders and sales at Wahana Ritel Honda Ciracas, along with challenges faced by consumers and sales in the manual ordering and sales processes. In this study, the System Development Life Cycle (SDLC) Waterfall method is employed, anticipating that the application will provide an effective solution to enhance the management of motorbike ordering and sales data, improve operational efficiency, and reduce the risk of human errors. Application testing through a questionnaire with the participation of 30 respondents indicates a high level of efficiency and effectiveness, with a score reaching 79.6%. The application proves to be efficient and effective, offering the desired solutions for users. It enables consumers to easily order motorbikes through Android devices, provides comprehensive information about products, and allows real-time interaction between consumers and sales. With a user-friendly interface, this application not only enhances the efficiency of the motorbike ordering and sales processes but also efficiently manages and stores consumer data. As a result, the application is recognized as a reliable solution to meet the needs of motorbike ordering and sales at Wahana Ritel Honda Ciracas